2022
DOI: 10.3390/ijerph19127465
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Time Perspectives Measured under the Dramatically Changing Socioeconomic Conditions during the Ukrainian Political Crises in 2014/2015

Abstract: The characteristics of the individual’s time perspective in relation to changes in social, economic, and political conditions are of major conceptual interest. We assessed the time orientations of 1588 Ukrainian students living in two different regions (western and south-eastern Ukraine) with the Zimbardo Time Perspective Inventory (ZTPI) before (2010–2013) and during (2014–2016) the socioeconomic, political, and military crises which started in 2014, eight years before the war in 2022. We applied ANOVAs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
3
0
2
Order By: Relevance
“…The differences proposed by O. Senyk et al (2022) in the study of time perspective under changed socio-economic conditions were taken into account. In the final variant, the version adapted to the Ukrainian sample by O. Senyk (2012) was applied.…”
Section: Olesia Smolinskamentioning
confidence: 99%
“…The differences proposed by O. Senyk et al (2022) in the study of time perspective under changed socio-economic conditions were taken into account. In the final variant, the version adapted to the Ukrainian sample by O. Senyk (2012) was applied.…”
Section: Olesia Smolinskamentioning
confidence: 99%
“…Consequently, there is a constant interplay between objective sensory stimuli and our subjective interpretation of them [ 12 , 79 , 80 ], also in terms of time perspective [ 81 , 82 ]. For example, a recent study of Ukrainian youth demonstrated how the 2014/2015 political crisis affected participants’ time perspectives with increasing or decreasing the negative present orientation and positive future orientation according to how directly they suffered from the situation [ 83 ]. Similarly, Kosak and colleagues [ 84 ], found how during the outbreak of COVID-19 a relative deceleration of time passage was generally associated with negative affect and social isolation; a relative acceleration was associated with an increase in routine in daily life.…”
Section: Conclusion Limitations and Future Studiesmentioning
confidence: 99%
“…The phenomena "temporality" and "psychological well-being" in terms of adolescence under the current social transformations (Kovtunyk et al, 2023;Senyk et al, 2022) are not defined clearly and regarded partially as a latent mental resource which requires not only empirical examination, but also operationalization in educational process . Sometimes perfect conditions for obtaining education, ideal up-to-date real and virtual educational spaces, modern interactive technologies, librariestransformers, co-working centers, innovative applications, educational development programs and pedagogical methods do not have a desirable effect.…”
Section: Introductionmentioning
confidence: 99%
“…Операціоналізація таких психологічних змістових параметрів навчально-професійної діяльності, як темпоральність і психологічне благополуччя є своєчасною і знаходиться у площині постійної уваги дослідників. Феномени "темпоральність" і "психологічне благополуччя" осіб юнацького віку в соціальних трансформаціях сьогодення (Kovtunyk et al, 2023;Senyk et al, 2022), не мають однозначного тлумачення і почасти залишаються латентним ментальним ресурсом, який потребує не тільки емпіричного тлумачення, але й операціоналізації в освітній процес . Подекуди ідеальні умови для опанування освіти, сучасні ідеальні віртуальні й реальні простори для навчання, сучасні інтерактивні засоби, бібліотеки-трансформери, коворкінг-центри, інноваційні застосунки, навчально-розвивальні програми і педагогічні технології не дають бажаного ефекту.…”
Section: Introductionunclassified